El rostro de eros : la filosofía del amor de Vladimir Solov'ev y sus aportes a la fenomelogía del eros - Garrido-Maturano, Ángel E. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2002)
The first part o f the artic le exam ines the phenomenological kem in the interpretation of erotical love given by the Russian philosopher Vladimir Solov’ev. In the second part, on the basis of the horizon of comprehension opened by Solov’ev, the author advances his own hermeneutics of the phenomenon. This interpretation attempts to elucídate the difference between eros and agape and the religiousness intrinsic to eros.